Classroom management : models, applications, and cases - Manning, M. Lee; Bucher, Katherine Toth, 1947- (Boston : Pearson, 2013)
In Classroom Management; Models, Applications, and Cases, Third Edition, pre-service teachers and administrators are given a wealth of information and activities that will prepare them to develop and apply a personal classroom management philosophy. Using a models approach, Manning and Bucher present a thorough discussion of the theories, models, and philosophies of classroom management; tackle the growing problems of school violence and bullying(including the'safe school' movement and cyber-bullying); and give thoughtful discussion to diversity and classroom management. Accessible and practical, this book will help guide educators toward developing and applying a personal classroom management philosophy all their own that can be applied immediately in the classroom.
Chapter 1. Introducing the Concept of Classroom Management -- Chapter 2. Safe calssroom and safe schools -- Chapter 3. Foundations of classroom management: Skinner, Redl, and Wattenberg , Glasser, Gordon, and Ginott -- Chapter 4. Behavioral approaches to classroom management -- Chapter 5. Ecological approaches to classroom management -- Chapter 6. Self-regulating approaches to classroom management -- Chapter 7. Exploring the process-outcomes approaches to classroom management -- Chapter 8. Supportive approaches to classroom management -- Chapter 9. Community approaches to classroom management -- Chapter 10. Whole-school approaches to classroom management -- Chapter 11. Classroom management in inclusive classrooms -- Chapter 12. Cultural and gender diversity and classroom management -- Chapter 13. Developing your personal classroom management philosophy -- Chapter 14. Applying a management philosophy in your classroom
Includes bibliographical references (p. 279-290) and indexes.
Keywords: Classroom management; School discipline